Upaya Meningkatkan Kemampuan Vocabulary Dalam Mata Pelajaran Bahasa Inggris di SD/MI - Nasution, Nabila Amalia; Adila, Dinda; Harahap, Hikma Sari; Fhitriansyah, Iqbal; Amirul, Bani (Yayasan Daarul Huda Kruengmane, 2024)
Studying English has become an important requirement in the technological era,namely the Industrial is today. One effort in the process of introducing English in elementary schools is by learning and memorizing English vocabulary that can be done by teachers i nparticular. Learning English vocabulary will increase our ability to remember. One way or method for learning to improve English vocabulary is through games. Games are one of the most effective tools to be taught to children when they want to improve their English vocabulary. This method aims to improve English vocabulary by playing guess words through our gestures. That way we will learn tomemorize and understand the words conveyed. The more guesses are correct, then we can learn the vocabulary with fun. Therefore this gamemethod can be applied by teachers in the process of learning English in the classroom.